2011
DOI: 10.1177/0898264311421199
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence Rates of Dementia and Cognitive Impairment No Dementia in the Mexican Population

Abstract: Objective To estimate the prevalence and incidence of dementia and cognitive impairment without dementia (CIND) in the Mexican population. Methods The MHAS study is a prospective panel study of health and aging in Mexico with 7,000 elders that represent 8 million subjects nationally. Using measurements of cognition and activities of daily living of dementia cases and CIND were identified at baseline and follow up. Overall incidence rates and specific rates for sex, age and education were calculated. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
120
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(147 citation statements)
references
References 40 publications
13
120
1
13
Order By: Relevance
“…The prevalence rate found in this study is consistent with a previous report of 6.1% in a similar sample [14]. In our current study, we further divided the MCI subtypes into mcd-MCI and na-MCI.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The prevalence rate found in this study is consistent with a previous report of 6.1% in a similar sample [14]. In our current study, we further divided the MCI subtypes into mcd-MCI and na-MCI.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have reported prevalence based solely on screening tests. For example, two studies in which MCI was defined using a brief version of the Cross-Cultural Cognitive Examination reported a prevalence of 6.1-7.0% [13,14]. Hence, the primary goal of the current study was to estimate the prevalence of MCI and its subtypes in an elderly population, taking moderating factors into consideration including demographic factors and health status.…”
Section: Introductionmentioning
confidence: 99%
“…De entre ellas podemos mencionar la implementación de actividades para mejorar el contacto social, o la práctica de actividades físicas en grupo, las cuales han demostrado tener un efecto positivo en los AM con depresión 35 . Entre las limitaciones del presente trabajo debe señalarse que, si bien la población estudiada carece de representatividad nacional, la distribución de las características generales de esta población es similar a la reportada en encuestas nacionales, como la EN-SANUT 36 y la ENASEM 37,38 . Otra consideración es que mediciones como la soledad, la insatisfacción o la infelicidad pueden están relacionadas con el constructo de la depresión.…”
Section: Discussionunclassified
“…Only a few Mexican studies have included clinical and neuropsychological evaluations to identify different cognitive profiles in early stages of dementia. In Mexico, MCI has been poorly studied and its prevalence and incidence is varied, even in epidemiological reports 28 . A cross-sectional epidemiological study, called 10/66 Dementia Research Group, that included a large sample of middle-and low-income subjects, was carried out in Cuba, Dominican Republic, Mexico, Peru, Puerto Rico, Venezuela, China, and India with 15,376 Individuals aged 65+ without dementia.…”
Section: Discussionmentioning
confidence: 99%